Proyeksi Produksi dan Konsumsi Gula Pasir di Indonesia 2022 2025 serta Implikasinya terhadap Target Swasembada Nasional - Amaliya, Arina; Supriono, Agus; Yanuarti, Rizky; Aji, Joni Murti Mulyo; Ridjal, Julian Adam; Soejono, Djoko; Ibanah, Indah (Journal of Agribusiness, Social and Economic, 2025)
Research aims to forecast sugar production and consumption in Indonesia for 2022–2025 and analyze its implications for the national self-sufficiency target by 2025. The research method employs ARIMA (Autoregressive Integrated Moving Average) time series analysis using secondary data from BPS and the Ministry of Agriculture (1990–2021). Results indicate that sugar production in 2025 is projected to reach 2.72 million tons, while consumption will hit 8.45 million tons, resulting in a mere 32.19% self-sufficiency rate (far below the 90% target). Key constraints include stagnant sugarcane acreage, low yield (7%), and inefficient sugar mills. The study concludes that the 2025 target is unachievable without aggressive policy interventions, such as land expansion, productivity improvements, and industry modernization. These findings provide a basis for policymakers to redesign more realistic sugar sector strategies.